2006
DOI: 10.1097/01.jom.0000197859.46894.7d
|View full text |Cite
|
Sign up to set email alerts
|

Chromium VI-Induced Apoptosis in a Human Bronchial Epithelial Cell Line (BEAS-2B) and a Lymphoblastic Leukemia Cell Line (MOLT-4)

Abstract: Hexavalent chromium compounds are well-documented human carcinogens. In vitro experiments show Cr (VI) induces cell death by apoptosis by activating p53 protein. The aim of this study was to evaluate Cr (VI)-induced apoptosis in a human bronchial epithelial cell line (BEAS-2B) and in a lymphoblastic leukemia cell line (MOLT-4). Cr (VI) caused a dose- and time-dependent increase in the apoptosis rate in both cell lines. Western blotting showed increased p53 protein expression in MOLT-4 cells, but not in BEAS-2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…An induction of apoptosis in association with the activation of p53 protein in the late stage of apoptosis (3-24 h after exposure) was reported by Ye et al (1999) and Liu et al (2001) in A549 cells exposed to chromate. The apoptosis induction observed in our study on BEAS-2B confi rms the results found by Gambelunghe et al (2006), on the same cell line exposed to Cr(VI). The lower extent of apoptosis found in BEAS-2B in comparison with A549 cells could be correlated to the lack of p53 induction, that diminishes the cellular response to DNA damage through apoptosis (Gambelunghe et al, 2006), and/or to an activation of NF-κB, which plays a protective role against Cr(VI) induced apoptosis (Liu et al, 2001;Chen et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An induction of apoptosis in association with the activation of p53 protein in the late stage of apoptosis (3-24 h after exposure) was reported by Ye et al (1999) and Liu et al (2001) in A549 cells exposed to chromate. The apoptosis induction observed in our study on BEAS-2B confi rms the results found by Gambelunghe et al (2006), on the same cell line exposed to Cr(VI). The lower extent of apoptosis found in BEAS-2B in comparison with A549 cells could be correlated to the lack of p53 induction, that diminishes the cellular response to DNA damage through apoptosis (Gambelunghe et al, 2006), and/or to an activation of NF-κB, which plays a protective role against Cr(VI) induced apoptosis (Liu et al, 2001;Chen et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The apoptosis induction observed in the present study by morphological analysis has already been shown in some in vitro studies after 12-24 h exposure to Cr(VI) (Carlisle et al, 2000;Gambelunghe et al, 2006). The apoptosis induction found in our study on A549 cells, particularly evident after 24 h at the highest concentration, could be correlated with increased p53 levels and with inhibition of the transcriptional activity of NF-kB (Shumilla et al, 1998;Hodges et al, 2004), which is a critical factor governing cellular response, including apoptosis (Karin et al, 2002).…”
Section: Discussionsupporting
confidence: 67%
“…The c-Jun N-terminal kinase (JNK) is selectively activated in A549 cells by 10 μM Cr(VI), and pre-exposure of cells to N-acetylcysteine prevents this activation [68]. This level of Cr(VI) is also sufficient to alter the expression of dozens of genes [88] and to induce apoptosis in BEAS-2B (normal human bronchial epithelial) cells [89], and it causes extensive cell death in primary human fibroblasts [90].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, which demonstrates that potassium dichromate induces apoptosis in MOLT-4 cells, levels of apoptosis were assessed for a range of increasing doses and for different exposure times. 16 A similar approach was utilized to evaluate eventual effects on the synthesis of PS.…”
Section: Discussionmentioning
confidence: 99%
“…16 The synthesis of PS and the eventual conversion of newly synthesized PS in other phospholipids was studied by measuring the incorporation of [ 3 H]serine into PS and metabolically related phospholipids. The analysis of phospholipids present in the cell incubation medium permitted us to consider the possible release from the cells of membrane microvesicles containing newly synthesized PS.…”
mentioning
confidence: 99%